A Sentencing Effectiveness Assessment Form as a Normative Instrument for Supervisory-and-Observatory Judges under Indonesia’s 2025 Criminal Procedural Law - Novritsar Hasintongan Pakpahan; Binsar Pamopo Pakpahan (Legalis : Journal of Law Review, 2026)
Criminal Procedural Law 2025 limits the role of supervisory-and-observatory judge to ‘researcher’, when it’s supposed to analyze trial proceeding’s effectiveness in sentencing. Research question based on existing problem includes how could there be absence of evaluative mechanism for sentencing effectiveness in the 2025 Criminal Procedural Law and how does supervisory-and-observatory judge may suggest effective sentencing with sentencing effectiveness assessment form. The novelty of this research is its finding of recognizing the method of supervisory-and-observatory judge in improving effective sentencing based on criminal procedural law 2025 through sentencing effectiveness assessment form that contains realistic practical report that may be considered and used as decision consideration of trial judges. Previous research such as Putra’s research (2024) that concludes sentencing must focuses on justice and obedience to God, but it has not discussed about the existence of Criminal Procedural Law 2025. As normative research, this research studies normative problem of supervisory-and-observatory judges to remedy improper sentencing for the future by applying statute approach towards Criminal Procedural Law 2025 and conceptual approach of legal expediency and theory of prisonization. Result showed that supervisory-and-observatory judges may express result of redundant sentencing and the use assessment form to remedy improper sentencing. The conclusion of this research is that the role of supervisory-and-observatory judge must be applied optimally with direct consequence to penitentiary to optimize crime decrease. Implication of the research would be to stress active role of supervisory-and-observatory judge to suggest effective sentencing. The research novelty is sentencing effectiveness assessment form as a normative model.